If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + 0 + y + s + e = s * 0 Reorder the terms: 0 + a + e + s + y = s * 0 Remove the zero: a + e + s + y = s * 0 Reorder the terms for easier multiplication: a + e + s + y = 0s Anything times zero is zero. a + e + s + y = 0s Solving a + e + s + y = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1e' to each side of the equation. a + e + s + -1e + y = 0 + -1e Reorder the terms: a + e + -1e + s + y = 0 + -1e Combine like terms: e + -1e = 0 a + 0 + s + y = 0 + -1e a + s + y = 0 + -1e Remove the zero: a + s + y = -1e Add '-1s' to each side of the equation. a + s + -1s + y = -1e + -1s Combine like terms: s + -1s = 0 a + 0 + y = -1e + -1s a + y = -1e + -1s Add '-1y' to each side of the equation. a + y + -1y = -1e + -1s + -1y Combine like terms: y + -1y = 0 a + 0 = -1e + -1s + -1y a = -1e + -1s + -1y Simplifying a = -1e + -1s + -1y
| 0=8ln(6-0.2x) | | (2x+5)(6x-1)=210 | | 4x^2-6x-700=0 | | k(X^2+1)=2Kx-1 | | 2x-55=125 | | 5p-2p=-6p | | 2n-1=3m | | 2x+2y=58 | | a*e-4*s=y*4 | | 6x+2y=106 | | [5X+6]=4 | | (36x^4y^2)^1/2 | | 6.28r+r=64 | | -3x+17= | | 5n^2-8=6n | | 3/8(16y-8)=9-5(y-2) | | 5/32 | | x*y=143 | | 2u^2-4u-5=(u-4) | | (x+4)=8 | | x/4-1.3=-0.05 | | 3cos(2x)=2sin^2*2x | | 3(d+6)= | | 3z+9=2z+6 | | 28/h-28/h-8=4/h | | 5y=5-x | | =((a^2)(b^3))(-a^5) | | 0.5/40 | | 6.5x-3+x-1.9= | | x(x+2)=3(x+4)+18 | | x(x+2)=3(x+4)+1 | | 5b-5-11b-4= |